SOFT syndrome in a patient from Chile. Issue 3 (20th December 2018) - Saida, Ken; Silva, Sebastian; Solar, Benjamin; Fujita, Atsushi; Hamanaka, Kohei; Mitsuhashi, Satomi; Koshimizu, Eriko; Mizuguchi, Takeshi; Miyatake, Satoko; Takata, Atsushi; Miyake, Noriko; Matsumoto, Naomichi
Abstract : SOFT syndrome (MIM614813) is an extremely rare primordial dwarfism caused by biallelic mutations in the POC1A gene. It is characterized by prenatal short stature, onychodysplasia, facial dysmorphism, hypotrichosis, and variable skeletal abnormalities including hypoplastic pelvis and sacrum, small hands, and cone‐shaped epiphyses, as well as delayed bone age. To the best of our knowledge, only eight POC1A mutations have been reported in humans to date. We report a 7‐year‐old Chilean girl with SOFT syndrome arising from a novel POC1A mutation c. 649C>T, p.Arg217Trp. Although her clinical features were largely compatible with SOFT syndrome, hand X‐ray examinations at 3.5 and 6 years unexpectedly showed normal bone age. Automated bone age determination was performed using image analysis software, BoneXpert. This case highlights the importance of the accumulation of patients with POC1A mutations to further elucidate the detailed clinical features of SOFT syndrome.